Kebahagiaan Sejati Berdasarkan Mazmur 1:1-6 dan Kontribusinya Bagi Orang Percaya (International Forum of Researchers and Lecturers, 2024)
In the history of life, humans are creatures who always want to achieve something they want and when humans have it they feel it is happiness. Happiness is the main focus point of God creating humans but true happiness is focused on God's Love. God created humans to enjoy the love of God, that is true happiness, but as time goes by, after humans fall into sin, humans begin to drift away from true happiness and even live their lives in a hedonistic way. In this research the author used a descriptive research method of literature study by taking data from books and journals related to the discussion. So the author concludes that human happiness can only be received from God because it is eternal happiness.